O teste de caminhada de seis minutos detecta mudanças na aptidão cardiorrespiratória de idosos saudáveis, após um programa de exercícios aeróbio, restrito e combinado? - Santana, Marcos Gonçalves de [UNIFESP] (2010)
The aim of this study was to determine whether the six-minute walk test (6-MWT) can detecting changes in cardiorespiratory fitness in healthy elderly men, after 24 weeks of aerobic, resistance and combined exercise. Forth three sedentary elderly men, aged 65-75 years, were allocated on four groups: aerobic group (AG, n = 10), resistance group (RG, n = 12), combined group - aerobic+resistance (ARG, n = 10) and control group (CG, n = 11). The intensity on AG was between 50 and 75% heart rate reserve, on RG between 50 and 80% of one maximum repetition and on ARG the sessions was intercalated with aerobic (AG) and resistance (RG) exercises. The training frequency was 3 times/week. Aerobic fitness was assessing using a cardiorespiratory exercise test (CRET) and the 6-MWT. In the pre-intervention, there was a moderate and significant correlation of 6-MWT distance with the V& O2peak (r = 0,51; p < 0,001), and with the V& O2 ventilatory threshold - V& O2 VT (r = 0,39; p = 0,010). The 6-MWT V& O2 correlated with the V& O2peak (r = 0,67; p < 0,001). The longitudinal analysis showed a significant improve on V& O2peak of AG (% = 15,0 ± 9,1%) and ARG (% = 12,6 ± 10,4%) compared with CG (% = -0,8 ± 8,5%; p < 0,001). In the 6-MWT, there was a significant increase in distance walked on AG (% = 5,5 ± 5,3%), RG (% = 2,7 ± 5,2%) and ARG (% = 4,6 ± 2,8%) compared to CG (% = -3,0 ± 5,9%; p < 0,001). However, longitudinal analysis showed no significant correlation between the changes (post - pre-intervention) of 6-MWT distance with the changes on V& O2peak (AG: r = 0,57; p = 0,08 e ARG: r = 0,18; p = 0,63), and with the changes on speed in the VT (AG: r = - 0,12; p = 0,738 e ARG: r = -0,25; p = 0,481). Thus, we can conclude that the 6-MWT is not appropriate to evaluate the changes in cardiorespiratory fitness of healthy elderly men, after 24 weeks of intervention with aerobic, resistance or combined exercise.